Chinese Intergovernmental Relations and World Development: Origins and Impacts of Chinese Export Credits. Issue 12 (15th October 2017) - Prysmakova, Palina
ABSTRACT: Generously offering loans for development projects around the world, China has recently brought them to Eastern Europe, namely to Belarus. By reviewing relevant development literature and using Belarus as a case study, this article contributes to the debate on China's emergence as a source of investment and aid. It addresses four concerns: the tools used by China, the driving forces behind proactive investing behavior, the advantages and disadvantages for a recipient country, and the conditionality attached. The article demonstrates that Chinese export credits resolve a latent conflict of interests between the central and local governments by transferring Chinese businesses abroad. Meanwhile, the borrowers have to deal with extra costs, for instance, high expenses to maintain final facilities or the cost of Chinese labor adaptation. In Belarus, the situation is exacerbated by the language barrier and a general anxiety of the local population derived from the lack of experience with foreigners.